KEPEMIMPINAN PEREMPUAN BERDASARKAN SELF EFFICACY, EMOTIONAL INTELEGENCE DAN KOMPETENSI (PERBANDINGAN GENDER) - Rina Masruroh; Munir Nur Komarudin; Aris Budiman; Dodi Dodi (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
Currently, although there is an increase in the number of women's participation in various sectors, in the government sector there are still many women who experience obstacles to becoming leaders. Some of the obstacles faced include gender stereotypes, discrimination, multiple role demands and lack of access to resources. Apart from that, it is felt that research on women's leadership in regional government is still very minimal, so more in-depth research on women's leadership is needed. This research aims to analyze the factors that influence women's leadership in terms of self-efficacy, emotional intelligence and competence and compare them with men's leadership. Self efficacy is measured by magnitude, generality, strength. Emotional intelligence is measured by knowing one's emotions, managing emotions, one's own motivation, recognizing emotions in others, and handling relationships. Leadership competence is measured by knowledge, skills and attitude. This research uses a quantitative approach with descriptive verification methods and comparative analysis using the independent sample t-test. The research results show that the self-efficacy and competence of female leaders is higher than that of male leaders, but there are no significant differences, however, male and female leaders apparently have the same level of emotional intelligence